Work productivity in the digital payment era: the roles of the pospay application, competition, and electronic service quality - Surahman Surahman; Bachtiar Rifai S; Novelia Kiki Permatasari (Institute of Computer Science (IOCS), 2026)
This study examined the effects of the quality of the Pospay application system and the level of competition in the digital payment era on work productivity, with electronic service quality as a moderating variable. The study addressed the challenge of maintaining work productivity amid rapid digital payment development and increasing competition in postal services. A quantitative research approach was employed. The population comprised of users of the Pospay application at the Post Office of Pandeglang Regency. A purposive sampling technique was applied, resulting in 300 respondents. Primary data were collected through questionnaire distribution. The data were analyzed using statistical techniques to test direct and moderating effects among variables. The findings indicated that the quality of the Pospay application system had a significant effect on work productivity. The level of competition in the digital payment era also significantly influences work productivity. Electronic service quality significantly moderated the relationship between the quality of the Pospay application system and work productivity, as well as the relationship between competition and work productivity. These results emphasize the importance of system quality, competitive conditions, and electronic service quality in enhancing work productivity within digital payment services